Gender, Crime and Punishment: Evidence from Women Police Stations in India - Sofia Amaral; Sonia Bhalotra; Nishith Prakash (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We examine the impact of establishing women police stations (WPS) on reporting of gender-based violence. Using administrative crime data and exploiting staggered implementation across Indian cities, we find that the opening of WPS is associated with an increase in police reports of crimes against women of 29 percent, a result driven by domestic violence. This appears to reflect reporting rather than incidence as we find no changes in femicide or in survey-reported domestic violence. We also find some evidence of an increase in women's labor supply following WPS opening, consistent with women feeling safer once the costs of reporting violence fall.
Keywords: J12; J16; J78; K14; K31; K42; N92; I12; 330; women police stations; gender-based violence; women in policing; India